Robert barker memorial session: Leadership in plasma science and applications - Becker, K.; Godfrey, B.; Kunhardt, E.; Laroussi, M.; Ludeking, L.; Neuber, A.; Schamiloglu, E.; Woods, Andrew (Institute of Electrical and Electronics Engineers, 2015)
© 1973-2012 IEEE. This paper summarizes the Dr. Robert J. Barker memorial session at the IEEE International Conference on Plasma Science 2014. Each section summarizes progress in a plasma research area strongly influenced by Dr. Barker's leadership: 1) plasma medicine; 2) atmospheric-pressure plasmas; 3) high-power microwaves; 4) pulsed power; and 5) numerical simulation of plasmas. He had a profound influence on these and other plasma science applications, as well as on numerous individual researchers. He will be missed greatly.